TRADITIONAL FARMING PRACTICES AND WASTEWATER IRRIGATION FARMING IN PERIURBAN, ZAMBIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Studies on urban and peri urban agriculture in Zambia have not adequately tackled issues pertaining to farming practices in wastewater irrigation farming. The investigated the farming practices in relation to heavy metal contaminated wastewater irrigated farming at two peri urban areas in Zambia. The method comprised observation of crop cultivation activities at field plots located at intervals along transects established in the stratified land zones at the two study sites namely New Farm in Mufulira and Chilumba Gardens in Kafue. The results revealed that farming practices were characterised by traditional land management farming practices and traditional multiple cropping systems which were influenced by a combination of agro ecological factors as well as availability of heavy metal contaminated wastewater which has the potential to contaminate soils and crops. The farming practices were based on adaptation of traditional production systems to peri-urban wastewater irrigation farming which corifirmed the results from other developing countries.